HBR guide to being a great boss. - Jania, Carolyn; Menasche, Steven (Harvard business review guides., 2022)
Are you a good boss-or a great one? We know people don't leave jobs, they leave bosses. How can you be the type of boss that doesn't send employees running? One who makes your people happy to work for you? You've got the basics covered. But can you raise your leadership level to be a boss who develops trust with their employees? How do you create a culture where learning-and failing-are ok? Can you go beyond evaluating performance and distributing bonuses once a year to finding ways to regularly share productive feedback-and recognize great work-in ways that work for the people who work for you? You can meet the basic requirements of your job as leader and rise above to motivate the people on your team to do more-and be more-than they thought possible. Whether you're a first-time boss or you've been managing people forever and are looking for some new insights and inspiration, the HBR Guide to Being a Great Boss collects a variety of expert voices to share their advice on being a boss who sparks creativity, engagement, and collaboration. You'll learn how to: magnify your people's strengths; communicate effectively-and regularly-with your team; cultivate trust; help your employees find meaning in their work; challenge your people to reach beyond their current limit; help struggling employees improve; and bring out the best in your people-and yourself.